The position of crime victims in legislation of the Republic of Slovenia - Filipčič Katja (Temida)
In the last ten years the position of victims of crimes has been improved in Slovenia. In criminal law the model of restorative justice has been enacted and the hearing of sexual abused children at the court main hearing is not allowed. By this measure the secondary victimisation of abused children has been reduced. The changes in the other law, beside the criminal code and criminal procedure code, also have determined the position of victims. The most important new law is The law of preventing family violence witch does not contain any new incrimination or sanction. Its main goal is to coordinate activities of different agencies and provide the systematic approach to family violence. Slovenia also enacted special law about payment the restitution to victims of violent crimes. In Slovenia public opinion about offenders became more punitive and demands for harsher sentences are made in the name of victims rights and public safety.